The Effect of Graffito Drawing Techniques on Children's Visual-Spatial Intelligence in Kindergarten Miftahul Jannah Padang - Viuti Efendi; Farida Mayar (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Although visual-spatial intelligence is essential for early childhood development because it supports children’s understanding of space, shape, direction, color, and imagination, field observations indicate that this ability remains insufficiently developed. Many children still have difficulty understanding direction, distinguishing colors, and expressing imagination independently, as they tend to imitate examples provided by teachers. This study aims to determine the effect of drawing using the graffito technique on children’s visual-spatial intelligence at Miftahul Jannah Kindergarten, Padang. A quantitative approach with a quasi-experimental design was employed. The population consisted of all 20 children at Miftahul Jannah Kindergarten, with the sample selected through purposive sampling, comprising Group B1 as the experimental class and Group B2 as the control class. Data were collected through observation using a visual-spatial intelligence assessment instrument. Data analysis was conducted using statistical tests, including normality and homogeneity tests, followed by a t-test comparing pretest and posttest results in both groups. The findings indicate that children in the experimental class experienced greater improvement in visual-spatial intelligence than those in the control class, as shown by the difference between the pretest and posttest results. The data were normally distributed and homogeneous, with significance values greater than 0.05. The t-test produced a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. The study concludes that drawing using the graffito technique has a significant effect on improving children’s visual-spatial intelligence. These findings contribute to early childhood education by demonstrating the value of creative art-based activities in stimulating spatial understanding, color recognition, and imaginative expression, while providing practical implications for kindergarten teachers in designing more exploratory and developmentally appropriate learning activities.